Towards Blockchain Empowered Trusted and Accountable Data Sharing and Collaboration in Mobile Healthcare Applications - Liang, Xueping; Shetty, Sachin; Tosh, Deepak; Bowden, Daniel; Njilla, Laurent; Kamhoua, Charles (EAI Endorsed Transactions on Pervasive Health and Technology, 2018)
Enabled by mobile and wearable technology, personal health data delivers immense and increasing value for healthcare, benefiting both care providers and medical research. The secure and convenient sharing of personal health data is crucial to the improvement of the interaction and collaboration of the healthcare industry. Faced with the potential privacy issues and vulnerabilities existing in current personal health data storage and sharing systems, as well as the blockchain integration concerns summarized in this paper, an innovative user-centric health data sharing solution by utilizing a decentralized but permissioned blockchain is proposed to protect privacy and enhance access management, with the help of channel formation scheme supported by the blockchain. By developing a web application for Personal Health Data Management (PHDM) systems, the individuals are capable of synchronizing sensor data from wearable devices with online account and controlling data access from any third parties. A mobile application is deployed to collect health data from personal wearable devices, manual input, and medical devices, and synchronize data to the cloud for data sharing with healthcare providers and health insurance companies. To preserve the integrity of health data, a proof of integrity and validation, is made available to each record, which is permanently retrievable from cloud database and is anchored to the blockchain network. Moreover, for scalable and performance considerations, a tree-based data processing and batching method is adopted to deal with large data sets of personal health data collected and uploaded by the mobile platform. To enable a trusted data access record, the Intel Software Extensions technology is utilized to ensure the accountability for data access and token based access control scheme is enhanced with the trusted hardware. Analysis shows that the proposed approach provides user privacy and accountability with acceptable overhead and scalability.